Polylactic acid composite material with Pickering microsphere interwoven structure and preparation method of polylactic acid composite material

Oxidized nanobacterial cellulose was prepared by TEMPO oxidation method and composited with polylactic acid by Pickering emulsion method to form a microsphere interwoven structure, which solved the problems of low crystallinity of polylactic acid materials and poor compatibility of nanocellulose, and improved the mechanics of the material and The heat resistance performance achieves efficient improvement of PLA materials.

CN119144011APending Publication Date: 2024-12-17HAINAN YEGUO FOODS +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411117989.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

During the processing process, polylactic acid materials have low crystallinity, poor heat resistance, and poor compatibility with PLA matrix, resulting in insufficient hardness and mechanical properties in their applications.

Method used

The TEMPO oxidation method is used to prepare oxidized nanobacterial cellulose with high aspect ratio, and is compounded with polylactic acid through the Pickering emulsion method to form a microsphere interwoven structure, which improves the uniform dispersion and interwoven ability of nanocellulose in the PLA matrix and enhances the material Crystallinity and mechanical properties.

Benefits of technology

The high crystallinity and high mechanical properties of PLA materials are achieved, the heat resistance and barrier properties of composite materials are improved, and the use of nanomaterials is reduced, making it easy to operate and good controllability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144011A_ABST
    Figure CN119144011A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and provides a polylactic acid composite material with a Pickering microsphere interwoven structure and a preparation method of the polylactic acid composite material. The method specifically comprises the following steps: carrying out TEMPO oxidation reaction on bacterial cellulose, then carrying out nanocrystallization treatment, emulsifying an obtained oxidized nano bacterial cellulose aqueous suspension and a poly (3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of a polylactic acid main material, drying, and carrying out hot pressing to obtain the polylactic acid-poly (3-hydroxybutyrate-co-3-hydroxyvalerate) composite material. According to the invention, on the basis of the amphiphilic characteristic of the oxidized nano bacterial cellulose, hydrophobic modification is not needed, a polylactic acid system structure is stabilized in the composite material through network sphere interweaving by using a Pickering emulsification microsphere method, polylactic acid heterogeneous nucleation is induced by the nano size to promote crystallization, and the mechanical strength, heat resistance and barrier property of polylactic acid are improved. Meanwhile, by adding the biopolyester PHBV, the toughness and barrier property of the polylactic acid composite material are enhanced, and the biodegradability is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a Pickering microsphere interlaced structure polylactic acid composite material and a preparation method thereof. Background Art

[0002] Plastic products are widely used in the packaging field because of their advantages such as light weight, high strength, corrosion resistance, easy processing and molding, and low cost. However, the widespread use of traditional plastic products has brought about serious white pollution problems. Degradable plastics are the best solution to white pollution. They not only have the advantages of traditional petroleum-based plastics such as light weight, high strength, and easy processing, but can also be completely degraded in the environment, which can effectively solve the serious pollution problems caused by petroleum-based plastics from the root.

[0003] Polylactic acid (PLA), as a bio-based degradable plastic, has the advantages of high strength, high modulus, high transparency, etc., and can be widely used in packaging, textiles, medicine and other fields. However, polylactic acid is a semi-crystalline polymer material with a long crystallization time. After processing steps such as extrusion and film blowing, the crystallinity is not high, resulting in poor heat resistance and hard and brittle mechanical properties at room temperature. These shortcomings limit its practical application.

[0004] In order to improve the crystallization performance of PLA materials, a large number of studies have found that nanocellulose, as a heterogeneous nucleating agent, can promote the crystallization of PLA, and due to its high aspect ratio and excellent mechanical properties, it can also enhance PLA. At the same time, as a biomass material, nanocellulose will not destroy the biodegradability of PLA. However, the hydrophilicity of the large number of hydroxyl groups on the surface of nanocellulose and the strong self-association caused by the formation of intermolecular and intramolecular hydrogen bonds between hydroxyl groups make it poorly compatible with the hydrophobic PLA matrix and easy to agglomerate in the PLA matrix.

[0005] Usually, surface hydrophobic modification of nanocellulose can effectively improve the compatibility between PLA and nanocellulose. Various hydrophobic or amphiphilic small molecules are grafted onto the surface of nanocellulose through esterification, carbonization, silanization, etc. and form composite materials with PLA. Highly hydrophobic nanocellulose is evenly dispersed in the PLA matrix, which is beneficial to improve the crystallization and mechanical properties of PLA composite materials. However, the use of hydrophobic modification agents increases the cost on the one hand, and weakens the ability of cellulose fibers to cross-link into a network structure on the other hand. Because hydrophobic modification reduces aggregation by weakening the hydrogen bonding force between fibers, even if the dispersion problem of nanocellulose is solved, its enhancement effect is weakened. Therefore, a new method is needed to achieve low-cost composites of nanocellulose and polylactic acid while maintaining the ability of cellulose fibers to cross-link into a network structure.

[0006] There are many methods for toughening PLA, including chemical modification, physical modification, and composite modification. Polymer blending is considered to be the most effective and economical method. Early studies used polymers or elastomers from petroleum to toughen PLA, sacrificing sustainability and biodegradability. Therefore, many studies have been devoted to toughening PLA with renewable polymers, among which PHBV (poly (3-hydroxybutyrate-co-3-hydroxyvalerate)) is a biodegradable polyester polymer material obtained by microbial fermentation. It can be synthesized under appropriate conditions using specific microbial strains and is safe and environmentally friendly. However, the PHBV material itself has a narrow processing window, is easily thermally degraded, and has a high melt viscosity. Long-term melt blending may cause PHBV degradation, resulting in a decrease in the performance of the blended material. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects in the prior art and provide a Pickering microsphere interlaced structure polylactic acid composite material and a preparation method thereof.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing a Pickering microsphere interwoven structure polylactic acid composite material, comprising the following steps:

[0010] (1) subjecting bacterial cellulose to TEMPO oxidation reaction and then subjecting it to nano-treatment to obtain an oxidized nano bacterial cellulose aqueous suspension;

[0011] (2) Emulsifying the oxidized nanobacterial cellulose water suspension and the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of the polylactic acid main material to obtain a Pickering emulsion stabilized by the oxidized nanobacterial cellulose, and drying to obtain polylactic acid composite microspheres with the surface covered with oxidized nanobacterial cellulose, and hot pressing or injection molding to obtain the Pickering microsphere interwoven structure polylactic acid composite material.

[0012] Preferably, the system of the TEMPO oxidation reaction in step (1) is 2,2,6,6-tetramethylpiperidine N-oxide / sodium bromide / sodium hypochlorite, and the solvent of the TEMPO oxidation reaction is water;

[0013] The mass volume ratio of the bacterial cellulose, water, 2,2,6,6-tetramethylpiperidine N-oxide, sodium bromide and sodium hypochlorite is 5-7 g: 800-1200 mL: 90-100 mg: 0.5-0.7 g: 0.55-0.65 g.

[0014] Preferably, the temperature of the oxidation reaction in step (1) is 20-30° C. and the time is 3-6 hours.

[0015] Preferably, the concentration of the oxidized nano bacterial cellulose aqueous suspension in step (2) is 0.0001 to 0.0013 g / mL.

[0016] Preferably, the solvent of the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of the polylactic acid main material in step (2) is dichloromethane;

[0017] The mass volume ratio of the polylactic acid main material to poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and to dichloromethane is 0.05-0.15 g: 0.5-1.5 mL;

[0018] The mass ratio of the polylactic acid main material to the poly (3-hydroxybutyrate-co-3-hydroxyvalerate) is 7-8:2-3.

[0019] Preferably, in step (2), the volume ratio of the oxidized nano bacterial cellulose aqueous suspension to the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of polylactic acid as the main material is 2 to 4:1.

[0020] Preferably, the emulsification speed in step (2) is 10000-14000 rpm, and the time is 1-5 min.

[0021] Preferably, the hot pressing in step (2) is performed at a temperature of 180 to 200° C., a pressure of 8 to 12 MPa, and a time of 5 to 15 min.

[0022] Preferably, the injection molding temperature in step (2) is 180-200° C. and the pressure is 0.5-0.7 MPa.

[0023] The present invention also provides a Pickering microsphere interlaced structure polylactic acid composite material prepared by the preparation method of the Pickering microsphere interlaced structure polylactic acid composite material.

[0024] The invention provides a method for preparing a polylactic acid composite material with a Pickering microsphere interwoven structure, comprising the following steps: (1) subjecting bacterial cellulose to a TEMPO oxidation reaction and then subjecting it to a nano-treatment to obtain an oxidized nano bacterial cellulose aqueous suspension; (2) emulsifying the oxidized nano bacterial cellulose aqueous suspension and a poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution as a polylactic acid main material to obtain a Pickering emulsion stabilized by the oxidized nano bacterial cellulose, drying to obtain polylactic acid composite microspheres with surfaces covered with oxidized nano bacterial cellulose, and hot pressing or injection molding to obtain the polylactic acid composite material with a Pickering microsphere interwoven structure.

[0025] The beneficial effects of the present invention are as follows:

[0026] 1. The present invention relies on the high aspect ratio, amphiphilic oxidized nano bacterial cellulose prepared by the TEMPO oxidation method, and adopts a simple Pickering emulsion method to interweave network spheres in the composite material to stabilize the polylactic acid system structure, thereby solving the problem of poor compatibility between hydrophobic polylactic acid and hydrophilic oxidized nano bacterial cellulose. The operation is simple, the controllability is good, and the nano material is evenly distributed. When the same improved performance is achieved, the amount of nano material used is small.

[0027] 2. The high aspect ratio of oxidized nanobacterial cellulose is conducive to the formation of a network skeleton throughout the entire system during melt processing. On the one hand, it makes the nanocellulose evenly distributed in the polymer matrix and promotes the crystallization of polylactic acid; on the other hand, it gives the system high strength and high oxygen barrier properties, thereby improving the mechanical strength, heat resistance and barrier properties of the composite material.

[0028] 3. PHBV gives the system toughness. Compared with the traditional physical blending method, it constructs micron-sized microspheres, greatly reduces the dispersed size of PHBV in the PLA matrix, increases the compatibility of the multiphase system, and brings out the barrier advantages of PHBV. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The scanning electron microscope images of the oxidized nano bacterial cellulose and the unoxidized nano bacterial cellulose prepared in Example 2, (a) is the unoxidized nano bacterial cellulose, and (b) is the oxidized nano bacterial cellulose prepared in Example 2;

[0030] Figure 2 The scanning electron microscope images of the composite microspheres of Example 2, (a) is the composite microspheres of Example 2, (b) is the surface of the composite microspheres of Example 2;

[0031] Figure 3 It is a crystallinity diagram of pure polylactic acid, examples 1 to 3 and the composite materials of comparative examples 1 to 3;

[0032] Figure 4 It is the Vicat softening point temperature diagram of pure polylactic acid, Examples 1 to 3 and Comparative Examples 1 to 3 composite materials;

[0033] Figure 5 Graphs of gas permeability of pure polylactic acid, composite materials of Examples 1 to 3 and Comparative Examples 1 to 3, wherein (a) is a graph of oxygen permeability, and (b) is a graph of water vapor permeability;

[0034] Figure 6 It is a tensile strength diagram of pure polylactic acid, examples 1 to 3 and comparative examples 1 to 3 composite materials;

[0035] Figure 7 It is a graph of elongation at break of pure polylactic acid, composite materials of Examples 1 to 3 and Comparative Examples 1 to 3;

[0036] Figure 8 It is a stress-strain curve diagram of pure polylactic acid, Example 2 and the composite materials of Comparative Examples 1 to 3;

[0037] Fig. 9 This is a microscope image of the composite material of Comparative Example 3 in a molten state;

[0038] Fig.10 The crystallization behavior diagrams of pure polylactic acid and the composite material of Example 2; (a) is pure polylactic acid, and (b) is the composite material of Example 2. DETAILED DESCRIPTION

[0039] The present invention provides a method for preparing a Pickering microsphere interwoven structure polylactic acid composite material, comprising the following steps:

[0040] (1) subjecting bacterial cellulose to TEMPO oxidation reaction and then subjecting it to nano-treatment to obtain an oxidized nano bacterial cellulose aqueous suspension;

[0041] (2) Emulsifying the oxidized nanobacterial cellulose water suspension and the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of the polylactic acid main material to obtain a Pickering emulsion stabilized by the oxidized nanobacterial cellulose, and drying to obtain polylactic acid composite microspheres with the surface covered with oxidized nanobacterial cellulose, and hot pressing or injection molding to obtain the Pickering microsphere interwoven structure polylactic acid composite material.

[0042] In the present invention, the system of the TEMPO oxidation reaction in step (1) is 2,2,6,6-tetramethylpiperidine N-oxide / sodium bromide / sodium hypochlorite, and the solvent of the TEMPO oxidation reaction is water.

[0043] In the present invention, the mass volume ratio of the bacterial cellulose, water, 2,2,6,6-tetramethylpiperidine N-oxide, sodium bromide and sodium hypochlorite is preferably 5-7 g: 800-1200 mL: 90-100 mg: 0.5-0.7 g: 0.55-0.65 g, more preferably 5.5-6.5 g: 900-1100 mL: 92-98 mg: 0.55-0.65 g: 0.56-0.64 g, and more preferably 5.8-6.2 g: 950-1050 mL: 94-96 mg: 0.58-0.62 g: 0.58-0.62 g.

[0044] In the present invention, bacterial cellulose, water, 2,2,6,6-tetramethylpiperidine N-oxide and sodium bromide are mixed and stirred, sodium hypochlorite is added after sufficient dissolution, and then the pH is adjusted; the stirring speed is preferably 200-250 rpm, more preferably 210-240 rpm, and more preferably 220-230 rpm; the solution used for adjusting the pH is a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is preferably 0.4-0.6 M, more preferably 0.45-0.55 M, and more preferably 0.48-0.52 M; the pH is preferably adjusted to 10-10.5, more preferably 10.1-10.4, and more preferably 10.2-10.3; and then an oxidation reaction is carried out.

[0045] In the present invention, the temperature of the oxidation reaction in step (1) is preferably 20-30°C, more preferably 22-28°C, more preferably 24-26°C; the time is preferably 3-6h, more preferably 3.5-5.5h, more preferably 4-5h.

[0046] In the present invention, after the oxidation reaction is completed, centrifugal washing is performed until neutral, and then circulating homogenization is performed; the pressure of the circulating homogenization is preferably 800-1200 bar, more preferably 850-1150 bar, and more preferably 900-1100 bar; the time is preferably 5-15 min, more preferably 6-14 min, and more preferably 8-12 min; after the circulating homogenization is completed, an oxidized nano bacterial cellulose aqueous suspension is obtained.

[0047] In the present invention, the concentration of the oxidized nano bacterial cellulose aqueous suspension in step (2) is preferably 0.0001 to 0.0013 g / mL, more preferably 0.0002 to 0.0012 g / mL, and more preferably 0.00033 to 0.001 g / mL.

[0048] In the present invention, the solvent of the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of the polylactic acid main material in step (2) is dichloromethane.

[0049] The mass volume ratio of the polylactic acid main material to poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and to dichloromethane is preferably 0.05-0.15 g:0.5-1.5 mL, more preferably 0.06-0.14 g:0.6-1.4 mL, and more preferably 0.08-0.12 g:0.8-1.2 mL.

[0050] In the present invention, the mass ratio of the polylactic acid main material to the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is preferably 7-8:2-3, more preferably 7.2-7.8:2.2-2.8, and more preferably 7.4-7.6:2.4-2.6.

[0051] In the present invention, polylactic acid as a main material and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) are added into dichloromethane and stirred until completely dissolved to obtain a polylactic acid as a main material poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution.

[0052] In the present invention, the volume ratio of the oxidized nano bacterial cellulose aqueous suspension and the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of polylactic acid as the main material in step (2) is preferably 2-4:1, more preferably 2.5-3.5:1, and more preferably 2.8-3.2:1.

[0053] In the present invention, the emulsification speed in step (2) is preferably 10000-14000 rpm, more preferably 11000-13000 rpm, and more preferably 11500-12500 rpm; the time is preferably 1-5 min, more preferably 2-4 min, and more preferably 2.5-3.5 min.

[0054] In the present invention, the temperature of the hot pressing in step (2) is preferably 180-200°C, more preferably 185-195°C, more preferably 188-192°C; the pressure is preferably 8-12 MPa, more preferably 8.5-11.5 MPa, more preferably 9-11 MPa; the time is preferably 5-15 min, more preferably 6-14 min, more preferably 8-12 min.

[0055] In the present invention, the temperature of the injection molding in step (2) is preferably 180-200°C, more preferably 185-195°C, and more preferably 188-192°C; the pressure is preferably 0.5-0.7MPa, more preferably 0.55-0.65MPa, and more preferably 0.58-0.62MPa; the time is preferably 2-6s, more preferably 3-5s, and more preferably 3.5-4.5s.

[0056] The present invention also provides a Pickering microsphere interlaced structure polylactic acid composite material prepared by the preparation method of the Pickering microsphere interlaced structure polylactic acid composite material.

[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0058] Example 1

[0059] 6 g of bacterial cellulose was dispersed in 1000 mL of water, 96 mg of TEMPO and 0.6 g of NaBr were added and stirred at 25 °C, 0.62 g of NaClO was added to start oxidation, and 0.5 M NaOH solution was added dropwise to keep the pH of the suspension at 10-10.5. The reaction was completed after 3 h, and the suspension was centrifuged and washed several times until neutral, and then circulated and homogenized at a pressure of 1000 bar for 10 min to obtain an oxidized nano bacterial cellulose (TOBC) water suspension;

[0060] Add dry PLA and PHBV to CH 2 Cl 2 The mass ratio of PLA to PHBV is 7:3, and the mass of PLA / PHBV and CH 2 Cl 2 The ratio of PLA / PHBV was 0.1 g:1 mL. Pour the CH 2 Cl 2 solution, in which the TOBC suspension is mixed with the CH 2 Cl 2 The volume ratio of the solution was 3:1. The CH 2 Cl 2 After drying, composite microspheres were obtained, and hot pressed at 190°C and 10 MPa for 10 min to obtain a Pickering microsphere interwoven structure polylactic acid composite material (PLA / PHBV / TOBC composite material).

[0061] Example 2

[0062] 6 g of bacterial cellulose was dispersed in 1000 mL of water, 96 mg of TEMPO and 0.6 g of NaBr were added and stirred at 25 °C, 0.62 g of NaClO was added to start oxidation, and 0.5 M NaOH solution was added dropwise to keep the pH of the suspension at 10-10.5. The reaction was completed after 6 h, and the suspension was centrifuged and washed several times until neutral, and then circulated and homogenized at a pressure of 1000 bar for 10 min to obtain an oxidized nano bacterial cellulose (TOBC) water suspension;

[0063] Add dry PLA and PHBV to CH 2 Cl 2 The mass ratio of PLA to PHBV is 8:2, and the mass ratio of PLA / PHBV to CH 2 Cl 2 The ratio of PLA / PHBV was 0.1 g:1 mL. Pour the CH 2 Cl2 solution, in which the TOBC suspension is mixed with the CH 2 Cl 2 The volume ratio of the solution was 3:1. The CH 2 Cl 2 After drying, composite microspheres were obtained, and hot pressed at 190°C and 10 MPa for 10 min to obtain a Pickering microsphere interwoven structure polylactic acid composite material (PLA / PHBV / TOBC composite material).

[0064] Example 3

[0065] 6 g of bacterial cellulose was dispersed in 1000 mL of water, 96 mg of TEMPO and 0.6 g of NaBr were added and stirred at 25 °C, 0.62 g of NaClO was added to start oxidation, and 0.5 M NaOH solution was added dropwise to keep the pH of the suspension at 10-10.5. The reaction was completed after 6 h, and the suspension was centrifuged and washed several times until neutral, and then circulated and homogenized at a pressure of 1000 bar for 10 min to obtain an oxidized nano bacterial cellulose (TOBC) water suspension;

[0066] Add dry PLA and PHBV to CH 2 Cl 2 The mass ratio of PLA to PHBV is 8:2, and the mass ratio of PLA / PHBV to CH 2 Cl 2 The ratio of PLA / PHBV was 0.1 g:1 mL. Pour the CH 2 Cl 2 solution, in which the TOBC suspension is mixed with the CH 2 Cl 2 The volume ratio of the solution was 3:1. The CH 2 Cl 2 After drying, composite microspheres were obtained, and hot pressed at 190°C and 10 MPa for 10 min to obtain a Pickering microsphere interwoven structure polylactic acid composite material (PLA / PHBV / TOBC composite material).

[0067] Comparative Example 1

[0068] The difference between this comparative example and Example 1 is that the dichloromethane in the PLA / PHBV solution is directly volatilized and then hot-pressed at 190° C. and 10 MPa for 10 min to obtain the PLA / PHBV composite material.

[0069] Comparative Example 2

[0070] The difference between this comparative example and Example 2 is that only PLA is contained in the oil phase without adding PHBV.

[0071] Comparative Example 3

[0072] The difference between this comparative example and Example 2 is that the TOBC aqueous suspension is freeze-dried and melt-blended with PLA and PHBV, and the proportions of the components remain unchanged.

[0073] Performance Testing

[0074] The oxidized nano bacterial cellulose and the unoxidized nano bacterial cellulose prepared in Example 2 were observed, and the obtained SEM images are as follows: Figure 1 As shown, (a) is unoxidized nano bacterial cellulose, and (b) is oxidized nano bacterial cellulose prepared in Example 2; it can be seen from the figure that before TEMPO oxidation treatment, BC has a nano network structure, and the fiber length ranges from a few microns to hundreds of microns. After oxidation, the anhydroglucose unit is split, and the cellulose is decomposed into smaller nano fibrils, with the length reduced to hundreds of nanometers to a few microns.

[0075] The composite microspheres prepared in Example 2 and the surfaces of the composite microspheres in Example 2 were observed, and the obtained SEM images were as follows: Figure 2 As shown, (a) is the composite microsphere of Example 2, (b) is the surface of the composite microsphere of Example 2, Figure 2 It can be seen that the composite microspheres were successfully prepared in Example 2, and from (b), it can be seen that TOBC was tightly wrapped on the surface of the PLA / PHBV composite microspheres.

[0076] The crystallinity of pure polylactic acid, examples 1 to 3 and comparative examples 1 to 3 composite materials was tested. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that the crystallinity of pure PLA is 21.8%, the crystallinity of the composite material of Example 1 is 40.95%, the crystallinity of the composite material of Example 2 is 43.95%, the crystallinity of the composite material of Example 3 is 42.39%, and the crystallinity of the composite material of Comparative Example 1 is 26.59%, indicating that PHBV has a certain promoting effect on the crystallization of PLA; the crystallinity of the composite material of Comparative Example 2 is 49.62%, indicating that TOBC can greatly improve the crystallinity of PLA when using the Pickering emulsion method; the crystallinity of the composite material of Comparative Example 3 is 36.68%, indicating that TOBC can also be used as a nucleating agent to improve the crystallinity of the composite material during melt blending.

[0077] The Vicat softening point temperatures of pure polylactic acid, examples 1 to 3 and comparative examples 1 to 3 composite materials were tested. The results are as follows: Figure 4 As shown, from Figure 4It can be seen that the Vicat softening point temperature of pure polylactic acid is 64.6°C, the Vicat softening point temperature of the composite material of Example 1 is 125.1°C, the Vicat softening point temperature of the composite material of Example 2 is 145.6°C, the Vicat softening point temperature of the composite material of Example 3 is 148.5°C, and the Vicat softening point temperature of the composite material of Comparative Example 1 is 64.1°C, indicating that although the addition of PHBV slightly improves the crystallization performance of PLA, the heat resistance is not improved; the Vicat softening point temperature of the composite material of Comparative Example 2 is 165.2°C, and the Vicat softening point temperature of the composite material of Comparative Example 3 is 78.0°C, indicating that during melt blending, TOBC can only slightly increase the Vicat softening point temperature of the PLA composite material, and its effect of improving heat resistance is not as good as that of the Pickering emulsion method.

[0078] The oxygen permeability and water vapor permeability of pure polylactic acid, the composite materials of Examples 1 to 3 and Comparative Examples 1 to 3 were tested. The results are as follows: Figure 5 As shown in the figure, (a) is the oxygen permeability graph, and (b) is the water vapor permeability graph. It can be seen that the oxygen permeability and water vapor permeability of pure PLA are 143.77 cm 3 / (cm 2 ·24h·0.1MPa) and 27.19g / (m 2 ·24h), the oxygen permeability and water vapor permeability of Example 1 were 23.72cm 3 / (cm 2 ·24h·0.1MPa) and 17.50g / (m 2 ·24h), the oxygen transmission rate and water vapor transmission rate of comparative example 1 without TOBC were 27.17cm 3 / (cm 2 ·24h·0.1MPa) and 20.89g / (m 2 ·24h), this is because PHBV itself has better barrier properties than PLA, so adding PHBV alone can also improve the barrier properties of the composite material, but TOBC further reduces the barrier properties of the composite material. The oxygen permeability and water vapor permeability of Example 2 are 20.60cm 3 / (cm 2 ·24h·0.1MPa) and 22.08g / (m 2 ·24h). The oxygen transmission rate and water vapor transmission rate of comparative example 2 without adding PHBV were 16.49cm 3 / (cm 2 ·24h·0.1MPa) and 17.9g / (m 2 ·24h), this is because the crystallinity is higher when only TOBC is added. The oxygen permeability and water vapor permeability of Comparative Example 3 are 63.56cm 3 / (cm 2 ·24h·0.1MPa) and 30.63g / (m 2 ·24h), this is because during melt blending, although the composite material has high crystallinity, TOBC is also hydrophilic, which makes it easy to agglomerate in the hydrophobic PLA matrix, and the oxygen permeability is less reduced than that of the Pickering emulsion method, and the hydrophilic TOBC has poor water barrier effect, resulting in a water vapor permeability that is even higher than that of pure PLA. The oxygen permeability and water vapor permeability of Example 3 are 22.55cm 3 / (cm 2 ·24h·0.1MPa) and 23.87g / (m 2 ·24h).

[0079] The tensile strength of pure polylactic acid, examples 1 to 3 and comparative examples 1 to 3 composite materials was tested. The results are as follows: Figure 6 The elongation at break of pure polylactic acid, Examples 1 to 3 and Comparative Examples 1 to 3 composite materials is shown in Figure 7 As shown, it can be seen that the tensile strength of the composite material of Example 1 is 43.24MPa and the elongation at break is 48.34%. The tensile strength of the composite material of Comparative Example 1 is 37.11MPa and the elongation at break is 67.13%. This is because the Pickering emulsion method makes TOBC well dispersed in the PLA matrix, which plays a reinforcing role, so the tensile strength of Example 1 is higher. The tensile strength of the composite material of Example 2 is 51.04MPa and the elongation at break is 50.52%. The tensile strength of the composite material of Comparative Example 2 is 70.97MPa and the elongation at break is 6.14%, which is because PHBV can improve the toughness of the composite material. The tensile strength of the composite material of Comparative Example 3 is 35.91MPa and the elongation at break is 11.71%, which is because TOBC is still hydrophilic in nature, and it is easy to agglomerate in the PLA matrix by the melt blending method, resulting in stress weak points, so the tensile strength and toughness are reduced. The tensile strength of the composite material of Example 3 is 45.43MPa and the elongation at break is 26.79%.

[0080] The stress-strain curves of pure polylactic acid, Example 2 and Comparative Examples 1 to 3 composite materials are shown in Figure 8 As shown, it can be seen that when the Pickering emulsion method is used, TOBC has a reinforcing effect on the composite material, and the addition of PHBV improves the toughness of the composite material; the microscopic image of comparative example 3 in the molten state is as follows Fig. 9 As shown, it can be seen that when the melt blending method is used, the hydrophilicity of TOBC makes it easy to agglomerate in the PLA matrix, and it does not have a reinforcing effect.

[0081] The crystallization behavior of pure polylactic acid and the composite material of Example 2 was observed under a hot stage polarizing microscope at 120°C. Fig.10 As shown, (a) is pure polylactic acid, (b) is the composite material of Example 2, Fig.10 It can be seen that compared with pure polylactic acid, the composite material of Example 2 has a faster crystallization speed and smaller grains, and the crystallization is more complete, so the Vicat softening point temperature is high.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Pickering microsphere interwoven structure polylactic acid composite material, It is characterized in that It includes the following steps: (1) subjecting bacterial cellulose to TEMPO oxidation reaction and then subjecting it to nano-treatment to obtain an oxidized nano bacterial cellulose aqueous suspension; (2) Emulsifying the oxidized nanobacterial cellulose water suspension and the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of the polylactic acid main material to obtain a Pickering emulsion stabilized by the oxidized nanobacterial cellulose, and drying to obtain polylactic acid composite microspheres with the surface covered with oxidized nanobacterial cellulose, and hot pressing or injection molding to obtain the Pickering microsphere interwoven structure polylactic acid composite material.

2. The method for preparing the Pickering microsphere interwoven structure polylactic acid composite material according to claim 1, It is characterized in that The system of the TEMPO oxidation reaction in step (1) is 2,2,6,6-tetramethylpiperidine N-oxide / sodium bromide / sodium hypochlorite, and the solvent of the TEMPO oxidation reaction is water; The mass volume ratio of the bacterial cellulose, water, 2,2,6,6-tetramethylpiperidine N-oxide, sodium bromide and sodium hypochlorite is 5-7 g: 800-1200 mL: 90-100 mg: 0.5-0.7 g: 0.55-0.65 g.

3. The method for preparing the Pickering microsphere interwoven structure polylactic acid composite material according to claim 2, It is characterized in that The temperature of the oxidation reaction in step (1) is 20-30° C. and the time is 3-6 hours.

4. The method for preparing the Pickering microsphere interwoven structure polylactic acid composite material according to claim 1, It is characterized in that The concentration of the oxidized nano bacterial cellulose aqueous suspension in step (2) is 0.0001 to 0.0013 g / mL.

5. The method for preparing the Pickering microsphere interwoven structure polylactic acid composite material according to claim 1, It is characterized in that The solvent of the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of the polylactic acid main material in step (2) is dichloromethane; The mass volume ratio of the polylactic acid main material to the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and to the dichloromethane is 0.05-0.15 g: 0.5-1.5 mL; The mass ratio of the polylactic acid main material to the poly (3-hydroxybutyrate-co-3-hydroxyvalerate) is 7-8:2-3.

6. The method for preparing the Pickering microsphere interwoven structure polylactic acid composite material according to claim 1 or 5, It is characterized in that The volume ratio of the oxidized nano bacterial cellulose water suspension and the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) composite organic solution of polylactic acid as the main material in step (2) is 2 to 4:

1.

7. The method for preparing the Pickering microsphere interwoven structure polylactic acid composite material according to claim 6, It is characterized in that The emulsification speed in step (2) is 10000-14000 rpm, and the time is 1-5 min.

8. The method for preparing the Pickering microsphere interwoven structure polylactic acid composite material according to claim 7, It is characterized in that The hot pressing in step (2) is performed at a temperature of 180 to 200° C., a pressure of 8 to 12 MPa, and a time of 5 to 15 minutes.

9. The method for preparing the Pickering microsphere interwoven structure polylactic acid composite material according to claim 8, It is characterized in that The injection molding temperature in step (2) is 180-200° C. and the pressure is 0.5-0.7 MPa.

10. The Pickering microsphere interlaced structure polylactic acid composite material prepared by the method for preparing the Pickering microsphere interlaced structure polylactic acid composite material according to any one of claims 1 to 9.

Citation Information

Cited By

  • Mining area carbon sequestration method with miscanthus rhizomes cooperating with degradable mulching film

    CN120883869A